2023
DOI: 10.1021/acs.jafc.3c00260
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermostability and Catalytic Activity of Streptomyces mobaraenesis Transglutaminase by Rationally Engineering Its Flexible Regions

Abstract: Streptomyces mobaraenesis transglutaminase can catalyze the cross-linking of proteins, which has been widely used in food processing. In this study, we rationally modified flexible regions to further improve the thermostability of FRAPD-TGm2 (S2P-S23V-Y24N-E28T-S199A-A265P-A287P-K294L), a stable mutant of the transglutaminase constructed in our previous study. First, five flexible regions of FRAPD-TGm2 were identified by molecular dynamics simulations at 330 and 360 K. Second, a script based on Rosetta Cartesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…However, these TGase mutants were only synthesized in E. coli in small amounts, , which are unsuitable for industrial production and application. In this study, S.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these TGase mutants were only synthesized in E. coli in small amounts, , which are unsuitable for industrial production and application. In this study, S.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal stability and catalytic activity of S. mobaraensis TGase have been significantly improved through molecular modification, ,,,, such as the FRAPD-TGm2 constructed in our previous study. However, these TGase mutants were only synthesized in E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…38 A growing body of research has shown that protein stability does not necessarily come at the expense of enzyme−substrate affinity and catalytic activity. 9,32,39 To some extent, local stiffness may be compatible with overall flexibility, and there is no contradiction between improving the overall stability of the protein and enhancing its affinity and catalytic efficiency. In this study, three software designs, based on multiple algorithms, were used to design mutants, and then, potential adverse mutations were screened out, based on the biophysical characteristics of the calculated three-dimensional structure of the mutant proteins.…”
Section: Protein Structural Analysis To Rationalize the Improved Perf...mentioning
confidence: 99%